Letter to the editor for the article entitled ''The importance and prognostic effect of thyroid hormones in patients with transposition of the great arteries'' - Atasoy, Mustafa Selçuk; Müdüroğlu, Ayhan (The European Research Journal, 2025)
Dear Editor, We read the article in September 2024 issue of the European Research Journal by Arslanoğlu et al. entitled “The importance and prognostic effect of thyroid hormones in patients with transposition of the great arteries” with great interest. First of all, we congratulate the authors for their valuable contribution to the literature. We would like to point out some issues and ask some questions to the authors about the content of the article.